A feasibility study of using an Electronic Nose as a fruit ripeness measuring instrument - Siti Nordiyana, Md Salim; Ali Yeon, Md Shakaff; Mohd Noor, Ahmad; Abdul Hamid, Adom (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.